Умови існування оптимального керування для деяких класів диференціальних рівнянь на часових шкалах - Лаврова, О.Є. (Нелінійні коливання, 2016)
Рассматривается задача оптимального управления на конечных и бесконечных временных шкалах. Получены достаточные условия существования оптимального управления в терминах правых частей системы и функции, входящей в критерий качества. We consider a class of optimal control problems on finite and infinite time scales. Sufficient conditions for the existence of optimal control for such optimal control problems are obtained. These conditions are presented in terms of functions included in the right-hand side of the system and the functional.